Flavor Precursor and Volatile Compounds Formation of Unfermented Cocoa Beans Hydrolyzed by Papain - IBRAHIM, Nur Syamsi; HIDAYAT, Chusnul; UTAMI, Tyas; YANTI, Rini; WITASARI, Lucia (Food Science and Technology, 2024)
Fermentation is notably crucial stage in the production of cocoa flavor precursors. Nevertheless, some cocoa plantations in Indonesia skip fermentation as the raw material is relatively small, and the fermentation period is extremely long. This study aimed to improve the flavor precursors in unfermented cocoa beans (var. forastero). Unfermented cocoa beans were hydrolyzed using papain at different concentrations and incubation times. The conditions to obtain the highest degree of hydrolysis were 3.3 U/mL (papain conc.) at 10 h incubation. After papain treatment, it exhibited lower reducing sugars and polyphenol content than unfermented cocoa beans. Besides, hydrophobic amino acids such as phenylalanine, valine, leucine, and isoleucine was increased. After roasting, volatile compounds for chocolate aroma were also presented. However, pyrazines, aldehydes, and esters, were still less than those in fermented cocoa beans. The results proved that the papain hydrolysis of unfermented cocoa beans can improve their flavor precursors and volatile compounds.